Geoconservation of geological and mining heritage related to banded iron formation of Itabira group, Quadrilátero Ferrífero, Minas Gerais, Brazil: a challenging issue - CAVALCANTI, José Adilson Dias (2023)
The Quadrilátero Ferrífero is a mineral-rich region covering about 7,000 km2 in Central-Southern Brazil. It is known for its extensive gold and iron ore reserves, and for its historical cities. Many geological and mining sites related to gold mining and iron ore mining are in protected areas, and have been studied for preservation and use in educational and tourism projects, but at the same time, the region has suffered many pressures from mining companies and its preservation is in a constant state of alert. Recently, geoconservation studies have emphasised the value of geological and mining heritage, its importance for understanding the history of territorial occupation, as well as the geological evolution of our planet. For example, the Cauê Peak is the type-locality of the Cauê Formation, where six new minerals (arsenopalladinite, atheneite, isomertieite, palladseite, jacutingaite and palladinite) were identified in the Ausingle bondPd deposits which were listed by the International Mineralogical Association (IMA), and where the systemic iron mining activities began with the creation of the first mining company, the Brazilian Hematite Syndicate, in 1909. Since the 19th century, many of these geosites have been the target of research and educational field trips in the training of geologists and mining engineers at the Ouro Preto School of Mines and Federal University of Minas Gerais. These geosites can be used to explain the geological history in the Archaean-Paleoproterozoic boundary of the Quadrilátero Ferrífero (QF), the depositional environment of banded iron formations of the Cauê Formation, and also through the Transamazonian (2.1-1.94 Ga) and Brazilian (650-450 Ma) orogenies responsible for development of Ausingle bondPd and iron deposits. When observing the Cauê Peak, the Itabira Peak and the Curral Mountain, the different stages in the evolution of the anthropic landscape can be observed. The Cauê Peak has been transformed into an open pit mine, the Itabira Peak is surrounded from all sides by mining activities and the Curral Mountain undergoes processes for authorization of mining activities in an area that should be preserved.